Accessory belly of piriformis, as a cause of superior gluteal neurovascular entrapment - Bansal, Rimple; Kaushal, Subhash; Chhabra, Usha (International Journal of Research in Medical Sciences, 2017)
During routine dissection on 50 years old male cadaver, an accessory belly of piriformis was observed. This accessory belly was superior and parallel to the main piriformis muscle. This was associated with emergence of superior gluteal nerve and superior gluteal artery between the two bellies. Piriformis muscle and its relation to sciatic nerve has been suggested as a cause of piriformis syndrome. But interestingly in the present case, superior gluteal nerve was interposed between two bellies that may help the clinicians to establish a rare yet important cause of piriformis syndrome and a rare cause of undiagnosed chronic pain in gluteal region. As superior gluteal artery was also interposed, so this rare variation holds interest to surgeons especially in isolated buttock claudication despite otherwise normal vascular investigations.